Discovery and characterization of the novel conotoxin Lv1d from Conus lividus that presents analgesic activity. (30th April 2021) - Qiang, Yuanyuan; Wu, Yun; Zhao, Di; Zhao, Boyao; Wang, Feng; Ren, Shuanglai; Wen, Yujun; Gu, Jinhai; Zhang, Lianxiang; Liu, Kunmei; Niu, Jianguo; Wang, Lei
Abstract: Cone snails are predatory gastropod mollusks that are distributed in all tropical marine environments and contain small peptides (conotoxins) in their venom to capture prey. However, the biochemical and molecular aspects of conotoxins remain poorly understood. In this article, a novel α4/7-conotoxin, Lv1d, was obtained from the venom duct cDNA library of the worm-hunting Conus lividus collected from the South China Sea. The cDNA of Lv1c encodes a 65 residue conopeptide precursor, which consists of a 21 residue signal peptide, a 27 residue Pro region, and 17 residues of mature peptide. The mature peptide Lv1d was chemically synthesized according to the sequence GCCSDPPCRHKHQDLCG. It was found that 10 μM Lv1d can completely inhibit frog sciatic nerve-gastrocnemius muscle contractility within 60 min. Moreover, 100 μg/kg Lv1d showed good analgesic effects in mouse hot plate model and formalin test. Patch clamp experiments showed that 5 μM Lv1d can inhibit the cholinergic microexcitatory postsynaptic currents (mEPSCs) requency and amplitude of projection neurons in Drosophila. In conclusion, the synthesis of Lv1d and its biological and physiological data might contribute to the development of this peptide as a novel potential drug for therapeutic applications. This finding also expands the knowledge of the targeting mechanism of the α4/7-subfamily conotoxins. Highlights: This is first time to report the molecular structure and biological function of a novel alpha-conotoxin Lv1d. Lv1d can inhibit frog sciatic nerve-gastrocnemius muscle contractility. Lv1d has shown good analgesic effects in mouse hot plate model and formalin test. Lv1d can inhibit frequency of cholinergic microexcitatory postsynaptic currents of projection neurons in Drosophila.